CONSUMER PERSPECTIVE REGARDING DRIED TROPICAL FRUITS IN TURKEY - CINAR, G. (Italian Journal of Food Science, 2018)
The purposes of this study are to evaluate the tropical fruit (banana, kiwi, pineapple) preferences of consumers in Turkey and their willingness to pay and to assess the factors that affect this willingness to pay. In this context, tropical fruit products were presented in packages of 50 grams to 386 individuals who had never tasted these products before, and after the products had been tasted, surveys were administered. The findings revealed that dried banana has sensory issues related to hardness and taste and that dried kiwi has sensory issues related to taste and odour. The results show that improving the taste characteristics and increasing the emphasis on health while promoting the products could have a positive impact on increasing the demand for these products in Turkey.